Study protocol: an observational study of distress, immune function and persistent pain in HIV - John A Joska; Mark R Hutchinson; Maia Lesosky; Victoria J Madden; Ncumisa Msolo; Luyanduthando Mqadi; Gillian J Bedwell; Jonathan Grant Peter; Romy Parker; Andrew Schrepf; Robert R Edwards (BMJ Open)
Introduction Many people with HIV report both distress and pain. The relationship between distress and pain is bidirectional, but the mechanisms by which distress exacerbates pain are unclear. The inflammatory response to challenge (inflammatory reactivity, IR) may be a partial mediator, given that neuroimmune interactions provide a substrate for IR to also influence neurological reactivity and, thus, pain-related neural signalling. This prospective, observational, case–control study will characterise the relationships between distress, IR, pain-related signalling as captured by induced secondary hyperalgesia (SH), and pain, in people with HIV who report persistent pain (PP) (cases) or no pain (controls).Methods and analysis One hundred people with suppressed HIV, reporting either PP or no pain, will be assessed two or four times over 6 months. The primary outcomes are distress (Hopkins 25-item symptom checklist), IR (multiplex assay after LPS challenge), and PP (Brief Pain Inventory), assessed at the baseline timepoint, although each will also be assessed at follow-up time points. Induced SH will be assessed in a subsample of 60 participants (baseline timepoint only). To test the hypothesis that IR partly mediates the relationship between distress and pain, mediation analysis will use the baseline data from the PP group to estimate direct and indirect contributions of distress and IR to pain. To test the hypothesis that IR is positively associated with SH, data from the subsample will be analysed with generalised mixed effects models to estimate the association between IR and group membership, with SH as the dependent variable.Ethics and dissemination Information obtained from this study will be published in peer-reviewed journals and presented at scientific meetings. The study has been approved by the Human Research Ethics Committee of the University of Cape Town (approval number: 764/2019) and the City of Cape Town (ref: 24699).Trial registration number NCT04757987.